Local Wisdom in the Serat Menak Lare as Teaching Materials in Secondary Schools (A Study of Literature Anthropology) - Arief Rahmawan; Mipa Tiyasmala (Javanologi: International Journal of Javanese Studies, 2023)
Local wisdom as part of the cultural values possessed by certain communities is considered as a form of defense of culture against incoming foreign cultures. This study aims to describe (1) the aspects of local wisdom in Serat Menak Lare; (2) the most prominent cultural aspects contained in Serat Menak Lare; (3) the relevance of Serat Menak Lare with Indonesian language learning in senior high school. The research type was descriptive qualitative study with an anthropological literary study approach. The source of data was taken from the book Menak Lare I-IV by R. Ng. Yasadipura I which has been transliterated and translated by Sulistijo HS. The data collection technique used is intensive reading and note-taking. The sampling technique used is purposive sampling which is analyzed by interactive analysis model. The results of the research in the form of local wisdom contained in Serat Menak Lare can be identified in the form of the names of figures, animals, plants, and adjustments to the description of the place setting. The cultural aspects that stand out in Serat Menak Lare are the system of tools and equipment for human life, the arts, and the religious system. Equipment that is often found is palace equipment and war equipment. Local wisdom in the arts is in the form of gamelan musical instruments, dance, and Javanese-style architecture. The religious system found is the nuances of the Islamic religion. Furthermore, Serat Menak Lare is very relevant to be used as an alternative study material of Indonesian language learning in high school/equivalent.Keywords: local wisdom, Menak Lare, literary anthropology